Kecenderungan Berperilaku Menyakiti Diri Sendiri (Self Harm) pada Remaja SMA - Putri, Mahesya Asril; Afdal, Afdal (Lembaga Yasin AlSys, 2024)
This research is motivated by a phenomenon that occurs in adolescents, where self-harming behavior is behavior carried out to overcome emotional disturbances or emotional pain by hurting oneself without any intention of committing suicide. This research aims to (1) Describe the tendency of self-harm behavior of SMA X students in the city of Padang as a whole, (2) Describe the tendency of self-harm behavior of SMA X in the city of Padang in the aspect of self -punishment, (4) describing the tendency of self -harm behavior of high school students in Padang in the aspect of interpersonal influence. This research uses quantitative research methods with descriptive research type. The population of this study was 600 students with a sample of 240 students who were students at SMA X in the city of Padang. Sampling used proportionate random sampling technique. Data collection used a self-harm instrument with Likert scale measurements. Based on the research results, it shows that 133 students of SMA Students' self-harm behavior when viewed from the self-harm aspect is as follows: (1) The emotional regulation aspect in the